APLIKASI ANALISIS KIMIA KUANTITATIF UNTUK PEMANTAUAN KADAR OBAT (THEURAPETIC DRUGS MONITORING) - Dewi, Ni Made Amelia Ratnata (AMINA, 2019)
Theurapetic drugs monitoring (TDM) is used to adjust individual drug therapy. TDM purpose is to maximize the therapeutic effect and reduce the side or toxic effects of the drug. In general, TDM includes sample preparation, conducting drug analysis and interpreting the concentration of the drug. The development of analytical techniques resulted in the determination of pharmacokinetic characters by measuring drug concentrations in the blood more easily. Drug analysis can be done by spectrophotometric, chromatographic or immunoassay methods. Immunoassay could provide fast results and easy to use, but this method cannot distinguish between drugs that have similar structures. In addition, immunoassays are not available for all drugs monitored in clinical laboratories, so chromatographic methods such as GC, HPLC, GC/MS, and HPLC / MS can still be applied to TDM.